Euler-Maclaurin Method for Approximating Solutions of Initial Value Problems - Alomari, Mohammad W.; Batiha, Iqbal M.; Anakira, Nidal; Jebril, Iqbal H.; Momani, Shaher; Alkasasbeh, Wala’a Ahmad (Association for Scientific Computing Electronics and Engineering (ASCEE), 2025)
This work is dedicated to advancing the approximation of initial value problems through the introduction of an innovative and superior method inspired by the Euler-Maclaurin formula. This results in a higher-order implicit corrected method that outperforms Taylor’s and Runge–Katta’s methods in terms of accuracy. We derive an error bound for the Euler-Maclaurin higher-order method, showcasing its stability, convergence, and greater efficiency compared to the conventional Taylor and Runge-Katta methods. To substantiate our claims, numerical experiments are provided, highlighting the exceptional efficiency of our proposed method over the traditional well-known methods.